(untitled) (Research, Society and Development, 2020)
The aim of this study was to know and describe the bioecology of Centropomus undecimalis (Bloch, 1792), as to its local nomenclature, habitat, feeding, reproduction and migration, based on the knowledge of the actors of fishing, as well as to trace the socioeconomic profile of these workers. The data were obtained through semi-structured interviews with fishermen, masters and boat owners, between March and May 2019 in the municipality of Bragança, using the snowball technique. The data were tabulated and analyzed in spreadsheets using Microsoft Office Excel, Past and IRAMUTEQ software. The socioeconomic profile of the fishing players was similar in terms of age, education, time in fishing and income, except the last one, which varied significantly according to occupation / profession. This species is known locally as camurim, robalo and camurim-preto. It has being found along the Brazilian Amazon coast, distributed in 20 ethno-habitats. Some of these habitats, 49.1% are found in the coastal / marine environment, 47.1% in the estuarine and 3.8% in the freshwater sector. They feed, preferably on fish, followed by crustaceans and insects. This species reproduces throughout the year, however, with greater frequency between the months of June and December (rainy-dry transition period and dry period). Migration occurs due to local seasonality, life stage and habitat, influencing food, reproduction and growth. The results presented, from an integrated perspective of knowledge, can be a key element in the starting point for the management and conservation of this species on the Brazilian Amazon coast.